Chief executive officer characteristics and discretionary accruals in an emerging economy - Marwan Altarawneh; Rohami Shafie; Rokiah Ishak; Belal Ali Abdulraheem Ghaleb (Cogent Business & Management, 2022)
The main aim of the current study is to examine the effect of Chief Executive Officer (CEO) characteristics on earnings management proxied by discretionary accruals. The study used 1,957 firm-year observations listed in Bursa Malaysia for the period from 2012 to 2016. Panel data method is used to examine the established hypotheses. The results show a significant negative association between CEO tenure, network, and gender and discretionary accruals. These results suggest that CEOs with more extended periods serving in the firm, CEOs with several external directorships, and female CEOs are more rigorous in improving their strategic decisions and are less likely to engage in earnings management. Hence, they are associated with high financial reporting quality (FRQ). However, there is no significant relationship between CEO expertise, CEO age and discretionary accruals. The results are robust to an alternative measure of discretionary accruals. Therefore, the current study extends the FRQ and corporate governance literature by investigating the impact of CEO characteristics on earnings quality and, consequently, FRQ. The results are important for policymakers, stockholders, and market participants in identifying the importance of CEO characteristics in producing high FRQ.
Keywords: 650; accruals; CEO characteristics; Earnings management; Malaysia